Evaluation of National Immunization Technical Advisory Groups (NITAGs) of middle-income countries in the WHO European Region; a synopsis - Külper-Schiek, Wiebe; Mosina, Liudmila; Jacques-Carroll, Lisa A.; Falman, Annika; Harder, Thomas; Kakarriqi, Eduard; Preza, Iria; Badalyan, Arman; Sahakyan, Gayane; Romanova, Oxana; Shimanovich, Veronika; Musa, Sanjin; et al. (Frontiers in Public Health, 2025)
IntroductionA National Immunization Technical Advisory Group (NITAG) provides independent guidance to Ministries of Health (MoH) and policymakers, enabling them to make informed decisions on national immunization policies and practices. As of 2022, 50 of the 53 countries in the World Health Organization (WHO) European Region (the Region) had established a NITAG, with 58% of all NITAGs and 66% of those in middle-income countries (MICs) in the Region meeting all six WHO process indicators of NITAG functionality. However, many newly established NITAGs in MICs in the Region experience challenges in terms of their functioning, structure, and outputs.MethodsTo address these challenges and achieve the goal of evidence-informed decision making on immunizations, the WHO Regional Office for Europe and the Robert Koch Institute (RKI) implemented a project to strengthen the functioning of MIC NITAGs of the Region through comprehensive evaluations of nine NITAGs and development and implementation of improvement plans.ResultsAll evaluated NITAGs are formally established and complete the most important aspects of NITAG functioning. The main challenge for all NITAGs is the lack of a well-staffed Secretariat to establish annual workplans and develop NITAG recommendations following a standardized process.DiscussionThe evaluation identified NITAGs' strengths and challenges. Some challenges have been addressed through improvement plan implementation. WHO and RKI will continue to evaluate NITAGs and support development and implementation of improvement plans. WHO and NITAG partners will continue to provide training on the standardized recommendation-making process and advocate increased MoH support to NITAGs, including dedicated Secretariat staff.